Flexible piezoelectric nanogenerator based on [P(VDF-HFP)]/ PANI-ZnS electrospun nanofibers for electrical energy harvesting - Hemalatha Parangusan (6556133) (2022)
Abstract Over the past decade, piezoelectric nanogenerator have attracted much attention to harvest mechanical energy from abundant resources in nature. Here, the ZnS microspheres is prepared by hydrothermal method and core-shell structured PANI/ZnS microspheres are synthesized by in situ polymerization method and then used as filler for the preparation of flexible [P(VDF-HFP)] based piezoelectric nanogenerator. The flexible P(VDF-HFP)/PANI-ZnS piezoelectric nanogenerator is prepared by Electrospinning technique. The core-shell PANI/ZnS composite improves the content of electroactive phase in [P(VDF-HFP)] and significantly improves the interfacial polarization between the PANI/ZnS particles and polymer matrix. Among all the samples, [P(VDF-HFP)]/2 wt% PANI-ZnS composite nanofibers exhibited the high piezoelectric peak-to-peak output voltage of 3 V compared with the neat [P(VDF-HFP)] (~ 120 mV). In addition, the high dielectric constant is observed for the [P(VDF-HFP)]/2 wt% PANI-ZnS composite nanofibers. These results implies that the fabricated flexible and efficient piezoelectric nanogenerator can be utilized for energy harvesting system. Other Information Published in: Journal of Materials Science: Materials in Electronics License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s10854-021-05352-4